Tinjauan Hukum Islam pada Perempuan yang Menganut Tabattul Karena Pengembangan Karir (Desa Bonal Kecamatan Lubuk Barumun) - Nur Fitryani Siregar; Serina Hasibuan; Nur Hakimah Akhirani Nasution (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
The objectives of this study are to determine: 1) the considerations used in establishing the Islamic legal review of women who practice tabattul for career development in Bonal Village, Lubuk Barumun District; 2) how Islamic law views women who practice tabattul for career development in Bonal Village, Lubuk Barumun District; 3) the factors underlying women’s decision to choose tabattul for the sake of career advancement in Bonal Village, Lubuk Barumun District. This study employs a qualitative approach using a juridical-sociological method. The juridical approach is used to examine Islamic legal provisions concerning women who practice tabattul for career development, while the sociological approach is applied to understand the social reality of tabattul. The subjects of this research are the women in Bonal Village, whereas the objects of the research include the practices and community understanding regarding Islamic law on tabattul for women. The findings show that women who choose tabattul may be permitted in cases where marriage could potentially bring harm to their spouse or when they believe they are incapable of fulfilling marital responsibilities. The majority of the Bonal Village community understands that Islam provides concessions for women to practice tabattul. However, many are still unaware that tabattul is permissible in Islam as long as it does not cause harm and is chosen for legitimate reasons, including career development.